PENGARUH KEMANDIRIAN TERHADAP MINAT BERWIARAUSAHA MAHASISWA PENDIDIKAN EKONOMI - Hans Riwu Manu, Rolens Erens (Journal Economic Education, Business and Accounting, 2023)
Low interest in entrepreneurship is one of the crucial problems faced by various regions. One of the solutions that can be done to encourage interest in entrepreneurship is to increase the character of young people, especially self-regulated. Based on this description, this research is focused on looking at the contribution of independence to the interest in entrepreneurship by using a quantitative method (explanatory survey). The population of this study was students of economics education (Undana) with a total sample of 59. In the process, this study used a questionnaire of 30 statements consisting of 12 questions (x) and 18 questions (y) (valid and reliable). This study uses a simple regression analysis technique by first testing the classical assumptions. Based on this description, the results show that independence has a positive and significant effect on interest in entrepreneurship.